2022
DOI: 10.1017/langcog.2022.19
|View full text |Cite
|
Sign up to set email alerts
|

Picture perfect peaks: comprehension of inferential techniques in visual narratives

Abstract: The ability to reconstruct a missing event to create a coherent interpretation – bridging inference – is central to understanding both real-world events and visual narratives like comics. Most previous work on visual narrative inferencing has focused on fully omitted events, yet few have compared inference generation when climactic events become replaced with a panel employing numerous inferential techniques (e.g., action stars or onomatopoeia). These techniques implicitly express the unseen event while balanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 58 publications
0
0
0
Order By: Relevance
“…Indeed, the results from the ACC analyses suggested that participants with lower levels of autistic traits showed greater ACC, as well as longer RTs. Although we did not nd evidence of a speed-accuracy trade-off in our data, this proposal is in line with prior ndings that longer RTs are often associated with higher VLFI scores [23]. Interestingly, this performance modulation only occurs for those with lower levels of autistic traits; for those with higher levels of autistic traits, visual language uency did not modulate either ACC or RT.…”
Section: Discussion: Experimentssupporting
confidence: 90%
See 4 more Smart Citations
“…Indeed, the results from the ACC analyses suggested that participants with lower levels of autistic traits showed greater ACC, as well as longer RTs. Although we did not nd evidence of a speed-accuracy trade-off in our data, this proposal is in line with prior ndings that longer RTs are often associated with higher VLFI scores [23]. Interestingly, this performance modulation only occurs for those with lower levels of autistic traits; for those with higher levels of autistic traits, visual language uency did not modulate either ACC or RT.…”
Section: Discussion: Experimentssupporting
confidence: 90%
“…With regard to RT, we found that for those with lower levels of autistic traits, increasing visual language uency was associated with increased RTs for panel deletion identi cation. This nding suggests that having higher rates of experience with visual narratives may negatively in uence one's ability to determine where a panel was missing from, which is in line with prior inferencing research (see [23]).…”
Section: Discussion: Experimentssupporting
confidence: 84%
See 3 more Smart Citations